Bring-your-own device (BYOD) guidance: information security considerations and recommendations for Malaysian army in Peninsular Malaysia - Fikri Hanis Md Badarudin (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2022)
Bring Your Own Device (BYOD) is a new phenomenon in which employees connect their personal mobile devices to an enterprise network to gain access to corporate information and conduct daily business functions. The issues of BYOD and its security has received significant attention; thus, the research is being conducted in order to investigate the use of application of the new and trendy devices which can contributes to as many information, knowledges and connections as the All-in-One concept with the whole countries in the world. Then, BYOD guidance: information security consideration is the title that has been chosen for the research upon all the need and relevancies of the security information and knowledges for the benefits of the country, Malaysia in the midst of sciences and technology era. And, the key words applied in the research such as devices, facilities, security, military forces, etc. The objective of this study is to identify the level of information security consideration on the practice of BYOD in the organization, then, to recognize factors that should be considered in ensuring organization’s information is secured while enabling the use of BYOD and to emphasize the security risks which can be related to the use of BYOD in organizations. The respondent will be 200 respondents among the military forces who work in Malaysian Army among personnel of the Markas Pemerintahan Medan Barat Tentera Darat (MK PMBTD). This study uses a quantitative and qualitative research method using SPSS 25.0 to get the data from the respondent. The findings of this study show that Information Security Consideration is moderately and significant with Successful BYOD Practice (r=0.606, p=0.000) and Security Measure Implemented (r=0.711, p=0.000) strongly and significant with Successful BYOD Practice. Then, the Security Risk showed strongly and significant (r=0.720, p=0.000) with Successful BYOD Practice. Then, the Beta coefficient is 0.569, which is the greatest satisfaction with Security Risk and this corresponds with the highest t-statistic of 8.036. The research provides good analytical guidance on the conceptual security maintenance framework for BYOD implementation by enhancing IT security management. The research demonstrated that it is possible to create appropriate IT security model in order to enhance BYOD security management. Hence, through this beneficial approach, it will become an effective way to determine the factors which influence efficiency and effectiveness of BYOD practice.